ENT 530 Social Media Portfolio: Young Living / Muhammad Izzam Razali - Razali, Muhammad Izzam (2021)
Young Living has evolved into a global leader in essential oils and wellness products. With offices in Australia, Europe, Canada, Japan, and Singapore, as well as farms all over the world, the company is headquartered in Lehi, Utah. Young living inspired millions of individuals across the world to explore new ways to alter their lives by experiencing nature's gifts of wellness and harmony, creating abundance as Young Living distributors, and discovering new chances for lifelong transformation. Reasons why you buy Feather the owl are they don’t offer the same therapeutic and medicinal benefits. Most essential oils have expiration dates, Young Living oils do not. Young Living has been producing the finest quality oils for over 20 years and with over 180 different oils they have the greatest selection of singles & blends of any essential oil company.